Parent-administered Neurodevelopmental Follow up in Children After Picornavirus CNS Infections. Issue 10 (October 2021) - Stephens, Carol; Reynolds, Clare; Cremin, Molly; Barry, Rachel; Morley, Ursula; Gibson, Louise; De Gascun, Cillian F.; Felsenstein, Susana
Abstract : Background: Data on the neurodevelopment of children who experienced central nervous system (CNS) infections with enteroviruses (EV) or parechoviruses (hPeV) is scarce and mostly limited to follow up of short-term outcomes. Methods: Parents of children who presented between 2014 and 2019, underwent a lumbar puncture and whose cerebrospinal fluid was polymerase chain reaction positive for EV or hPeV, were asked to complete a care-giver-administered neurodevelopmental assessment tool (The Ages and Stages Instrument [ASQ3]). Clinical data of the infective episode were collected from patient notes. Results: Of 101 children, 43 (10 hPeV+, 33 EV+) submitted ASQ3 results. Median age at assessment was 38.9 months (interquartile range, 15.4–54.8), the follow-up interval 3 years (median 37 months; interquartile range, 13.9–53.1). Age, inflammatory markers, and cerebrospinal fluid pleocytosis during the infective event were not associated with ASQ3 scores. In 23 children (17 EV+, 6 hPeV+), no neurodevelopmental concerns were reported. Two more had preexisting developmental delay and were excluded. Of the remaining, 18/41 (43.9%) reported ASQ3 scores indicating need for monitoring or professional review in at least 1 category, not differing by pathogen (EV 14/31, 45.2%; hPeV 4/10, 40%; P = 0.71). Seven children will require formal review, scoring ≥2 SD below the mean in at least 1 category (6/31 EV+, 1/10 hPeV+, P = 0.7), 3 scored ≥2 SD below the mean in more than 1 area. Conclusions: Parent-administered developmental assessment of children with a history of early picornavirus infection of the CNS identified a subgroup that requires formal neurodevelopmental review. Wider application of community-based developmental screening will complement our understanding of the impact of CNS infections in early childhood. Abstract : Supplemental Digital Content is available in the text.